1990
DOI: 10.1148/radiology.176.2.2195596
|View full text |Cite
|
Sign up to set email alerts
|

Air-contrast barium enema studies after flexible proctosigmoidoscopy: randomized controlled clinical trial.

Abstract: The authors performed a randomized clinical trial to determine the effect of flexible proctosigmoidoscopy (FPS) on the quality of air-contrast barium enema (ACBE) studies performed on the same day and whether it mattered if air or carbon dioxide was used for endoscopic insufflation. One hundred twenty-one patients were randomly assigned to one of the following groups: Same-day studies were performed, with air used for insufflation, in group 1; same-day studies, with carbon dioxide, in group 2; and separate-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Eckhardt et al [12], using carbon dioxide for insufflation at FS, demonstrated that same-day FS and DCBE were feasible without impairing the quality of the DCBE. Marshall et al [14] found that it did not matter n = 78* *2 further ileorectal whether carbon dioxide or air was used for FS insufflation. On the other hand, Rodney et al [15] cancelled about one third of patients scheduled for same-day DCBE after FS, due to excessive bowel gas seen on a plain abdominal radiograph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eckhardt et al [12], using carbon dioxide for insufflation at FS, demonstrated that same-day FS and DCBE were feasible without impairing the quality of the DCBE. Marshall et al [14] found that it did not matter n = 78* *2 further ileorectal whether carbon dioxide or air was used for FS insufflation. On the other hand, Rodney et al [15] cancelled about one third of patients scheduled for same-day DCBE after FS, due to excessive bowel gas seen on a plain abdominal radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have reported success in performing FS and DCBE as a one-stage procedure with a single bowel preparation [9,10,[12][13][14]. We have instigated a combined FS/DCBE service within our radiology department and report here our initial experience in our first 80 patients.…”
mentioning
confidence: 97%
“…Radiologists often complain about residual air in the colon after failed colonoscopy or sigmoidoscopy prior to air-contrast barium enema (ACBE). However, the feasibility of same-day flexible sigmoidoscopy and ACBE is well established [5], and we have shown in a controlled trial that patients who had failed colonoscopies had ACBEs of equal quality regardless of whether the ACBE was performed on the same day or another day [6].…”
Section: Guest Discussants Replymentioning
confidence: 97%